(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to develop This study aims to develop a game model that can improve the basic locomotor movement abilities of lower-grade students at Inti Tondo State Elementary School (SDN). Basic locomotor movements such as walking, running, jumping, and hopping are fundamental skills that need to be developed early because they are the basis for subsequent physical activities. The research method used is research and development (R&D) with reference to the Borg & Gall model, which is modified into two stages, namely the preliminary stage and the development stage. The test subjects were students in grades I–III of SDN Inti Tondo. Data collection techniques used observation, questionnaires, and documentation that were validated by experts and tested through small and large-scale trials. The results of the study produced three game models, namely: (1) the S-M-S game (Fun, Enjoyable, Cool), (2) the Ninja Turtle game, and (3) the Cat’s Tail game. Based on the results of expert validation, the developed game model was declared suitable for use with a reliability coefficient ranging from 0.812–0.875. These findings indicate that the development of game models has proven effective in improving the basic locomotor movement abilities of lower-grade students.